DÉco in the city - Alexandria, Genilda (Revista UFG, 2017)
The images which follow are an invitation to journey along an asymmetric route, a passage through spaces built in a visual narrative of outstanding geometry. At times one is tempted to pause in front of the photograph and follow its straight lines and curves until it ends up in parapets, a facade, in the irons of a surround or a sculpture. The everyday familiar look sees things anew, and you might let escape a How did I not see that before? Then comes a desire to see. This desire can be satisfied (or stimulated) by the unique arrangement projected within the borders of the images which are presented on the following pages and which, for one other moment, have consumed the photographer observer. (...)